Peningkatan perekonomian Dusun Kesongo, Kabupaten Semarang dengan media boster kelengkeng - Amin, Muhammad; Hermalia, Nisa; Siregar, Habiburrahman; Bariyyah, Reyhana Khoirul; Ramadhan, Raihan Bintang; Suryanto, Suryanto (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
Improving the economic and agricultural quality value is an effort to carry out activities more effectively, encompassing both efficiency and result quality aspects. This process involves analyzing past activities, identifying areas for improvement, and implementing new strategies to achieve higher goals. In this context, economic education plays a crucial role in household financial management. In agriculture, the KKN program in Kesongo Village focuses on longan tree cultivation through fertilizer education using boosters. This program aims not only to enhance agricultural output but also to raise awareness about sustainable farming practices. The Participatory Action Research (PAR) method is applied in this program, involving the active participation of the community in planning and implementation. The positive response from the community shows new hope for increasing agricultural productivity through a collaborative and sustainable approach.